2016
DOI: 10.15829/1560-4071-2016-6-50-54
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Russian Version of Ds14 Score for Ischemic Heart Disease Patients

Abstract: 50Российский кардиологический журнал № 6 (134) | 2016 50НАДЕЖНОСТь И ВАЛИДНОСТь РУССКОязЫЧНОЙ ВЕРСИИ ШКАЛЫ DS14 У бОЛьНЫХ ИШЕМИЧЕСКОЙ бОЛЕзНьЮ СЕРДЦА Пушкарев Г. С., Кузнецов В. А., Ярославская е. и., Бессонов и. С.Цель. Цель исследования заключалась в оценке факторной, конструктной валидности, а также надежности русскоязычной версии шкалы ds14 у больных ишемической болезнью сердца (иБС). Материал и методы. В исследование было включено 977 пациентов с иБС (334 пациента с острым коронарным синдромом и 643 пацие… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…Therefore, studies on the prognostic value of personality type D in different regions remain relevant. It was previously shown that the Russian version of DS14 coincides with the English version in terms of reliability and internal structure, the validity of the design is confirmed by the results of correlation analysis [ 29 ].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, studies on the prognostic value of personality type D in different regions remain relevant. It was previously shown that the Russian version of DS14 coincides with the English version in terms of reliability and internal structure, the validity of the design is confirmed by the results of correlation analysis [ 29 ].…”
Section: Introductionmentioning
confidence: 70%
“…The evaluation of the psychological status was carried out using questionnaire DS14, in the preoperative period and postoperative period, validated in Russian [ 29 ]. The DS14 questionnaire comprises two subscales: negative affectivity (NA) and social inhibition (SI), containing seven questions each.…”
Section: Methodsmentioning
confidence: 99%
“…If the score was ≥10 points on both subscales, Type D personality was diagnosed [8]. Validation of the Russian version of the questionnaire was performed earlier in the group of patients with CAD [21]. Performed exploratory factor analysis demonstrated a two-factor structure of the questionnaire, explaining 45% of the total variance (29.1% – first factor and 15.9% – second factor).…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach’s α, related to internal consistency, was higher for NA scale (.78) than for SI scale (.74). Importantly, the corrected item-total correlation for item #3 “ I often talk to strangers ” (.21) was significantly lower than for the other 6 social inhibition items, and deletion of this item improved the internal consistency (Cronbach’s α) of the social inhibition subscale [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation